WHAT FACTORS DETERMINE INDONESIA ECONOMIC GROWTH AND HOW DOES THE U.S. AND CHINA TRADE WAR AFFECT IT? - Herenda, Agil Muhammad; SS, Vietha Devia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
This study aims to analyze the factors that determines economic growth in Indonesia and to see whether trade war does affects economic growth in Indonesia. The variable analyzed were exports, imports and inflation as independent variables using secondary monthly data from 2017 to 2020 as samples, and the variable of trade war itself as a dummy. Gross Domestic Product is used as a dependent variable to measure the economic growth. The statistical methods applied are descriptive statistics, classical assumption test, multiple regression model, and paired sample t-test. The findings showed that exports positively influenced economic growth, while imports and inflation does not. Trade war, however, has a favorable influence on trade war, showing a different result obtained from the paired sample t-test.